A novel method for fast sky conditions identification from global solar radiation measurements. (December 2020) - Lou, Siwei; Huang, Yu; Li, Danny H.W.; Xia, Dawei; Zhou, Xiaoqing; Zhao, Yang
Abstract: Sky conditions, and the corresponding luminance and radiance distribution patterns are essential to daylighting, energy and thermal environmental studies. The CIE Standard Skies define the overcast, partly cloudy, and clear sky conditions intuitively by rigorous luminance distributions, which are, however, usually determined by sophisticated and uncommon measurements (e.g. radiation in multiple vertical directions). This study proposes a simple approach to identifying the hourly sky conditions from the global horizontal irradiance ( E HG ) that is most widely accessible in weather stations with basic radiation measurement facilities. The sophisticated measurements are, therefore, avoided for simple applications. The partly cloudy sky, especially, is identified by the notable disparity of its E HG measurement from the theoretical cloudless condition. The proposed approach interprets the ISO/CIE Standard Sky conditions and their diffuse luminance and radiance distributions successfully. From the datasets at two sites with different climates, the approach correctly identifies 7% more sky conditions than a previous work when the direct beam and diffuse radiation measurements were not accessible. The model can thus be essential to solar energy studies for places with ground-based solar radiation measurements only. Highlights: The hourly ISO/CIE Skies were identified by the global irradiance series. Partly cloudy skies were identified by the disparity from theoretical cloudless cases. The approach is accurate for cases without direct and diffuse solar measurements. The approach is derived and supported by data of different climates.